Dynamic-MRI quantification of abdominal wall motion and deformation during breathing and muscular contraction. (April 2022) - Jourdan, Arthur; Rapacchi, Stanislas; Guye, Maxime; Bendahan, David; Masson, Catherine; Bège, Thierry
Highlights: Deformation quantification based on semi-supervised segmentation and registration. Contraction led to lateral muscles shortening, thickening and inward displacement. Maximal inhalation led to muscles lengthening with significant thickness decrease. During inhalation, large outward displacement of the rectus abdominis was observed. Perspectives for a clinical tool for the assessment of abdominal wall function. Abstract: Background and Objective: Biomechanical assessment of the abdominal wall represents a major prerequisite for a better understanding of physiological and pathological situations such as hernia, post-delivery recovery, muscle dystrophy or sarcopenia. Such an assessment is challenging and requires muscular deformations quantification which have been very scarcely reported in vivo. In the present study, we intended to characterize abdominal wall deformations in passive and active conditions using dynamic MRI combined to a semiautomatic segmentation procedure. Methods: Dynamic deformations resulting from three complementary exercises i.e. forced breathing, coughing and Valsalva maneuver were mapped in a transversal abdominal plane and so for twenty healthy volunteers. Real-time dynamic MRI series were acquired at a rate of 182 ms per image, then segmented semi-automatically to follow muscles deformation through each exercise. Circumferential and radial strains of each abdominal muscle were computed from the geometrical characteristics' quantification, namely the medial axis length and the thickness. Muscular radial displacement maps were computed using image registration. Results: Large variations in circumferential and radial strains were observed for the lateral muscles (LM) but remained low for the rectus abdominis muscles (RA). Contraction phases of each exercise led to LM muscle shortening down to -9.6 ± 5.9% during Valsalva maneuver with a 16.2 ± 9.6% thickness increase. Contraction also led to inward radial displacement of the LM up to 9.9 ± 4.1 mm during coughing. During maximal inhalation, a significant 10.0 ± 6.6% lengthening was quantified for LM while a significant thickness decrease was computed for the whole set of muscles (-14.7 ± 6.6% for LM and -7.3 ± 6.5% for RA). The largest displacement was observed for the medial part of RA (17.9 ± 8.0 mm) whereas the posterior part of LM underwent limited motion (2.8 ± 2.3 mm). Displacement rate and correlation between muscle thickness and medial axis length during each exercise provided insights regarding subject-specific muscle function. Conclusions: Dynamic MRI is a promising tool for the assessment of the abdominal wall motion and deformations. The corresponding metrics which have been continuously recorded during the exercises provided global and regional quantitative information. These metrics offer perspectives for a genuine clinical evaluation tool dedicated to the assessment of abdominal muscles function in both healthy subjects and patients.